FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAMPUAN SOCIAL PROBLEM SOLVING PADA REMAJA - Diah Utaminingsih (Jurnal Ilmu Pendidikan, 2012)
This research aimed is to investigate the effects of social support, optimism and gender on constructive social problem solving and dysfunctional social problem solving, furthermore to identify is there any singular social problem solving ability between two sexes, male and female. Research took place in several High Schools in Bandar Lampung with 861 participants are involved, 391 male and 470 female. Quantitative method involved three measurement scales. Besides that this research involved gender variable. Multiple correlation analysis, dummy regression and covariance analysis were being used as data analysis technique with SPSS 13.00 program. The results indicated that there is a significant influence between social support and optimism, but gender no effect influence on social problem solving. Effective contribution that given by social support and optimism on dysfunctional social problem solving is 18.8% (R square= 0.188). Effective contribution that given by social support and optimism on constructive social problem solving is 12,2% (R square= 0.122). Each variables gives effective contribution, they are: social support and optimism toward dysfunctional social problem solving are 12.42% and 6.38%. Furthermore social support and optimism on constructive social problem solving are 10.38% and 1.82%. Keywords: optimism and gender, social problem solving, social support